The corporation : rethinking the iconic form of business organization - Meyer, Renate E.; Leixnering, Stephan; Veldman, Jeroen (Emerald Publishing Limited, 2022)
For more than a century, the corporation has shaped our thinking of organizations. This deeply institutionalized form is still regarded as both the iconic business organization and the core structural unit of our economic order. Today, however, it stands at a crossroads. Economic, social, and environmental failures of the recent past as well as misconduct and scandals are widely associated with deficits of the corporate form and its governance. The Corporation engages with current issues of the corporation as an institutionalized organizational form, approaching the concept from the backgrounds of organization theory, law, and economics, combining different theoretical views and empirical approaches. This volume addresses the corporation's entanglement with capitalism, examines a spectrum of constitutive features and purposes of the corporate form, offers historical perspectives on its emergence, and provides reflections on its future development. Encouraging you to rethink the corporation, each contribution also adds to the conceptual development of the corporate form as the iconic business organization.
Includes index.
Keywords: Corporations -- Sociological aspects.; Social Science -- Sociology -- General.; Sociology: work & labour.; elektronické knihy; electronic books